Mende Interferometer: From the Experimental Refutation of the Lorentz Transformations and the Principles of the Invariance of the Speed of Light to New Prospects for the Development of Passive Radar (Global Journal of Science Frontier Research, 2018)
A new type of interferometer has been developed that uses the principle of mechanical beam division. With its help, the time constant of the wavelength of the laser beam, which does not depend on the velocity of the generator or mirror moving along the harmonic law, has been experimentally observed. The combination of this new effect with the known Doppler effect indicates the classical addition of the speed of light in this case with the speed of its source, which violates the principle of the invariance of the speed of light of the theory of relativity. Due to the detected effect, the use of a developed interferometer in passive radar opens up new prospects for its development.
Keywords: the special theory of relativity; interference; laser; michelson interferometer; doppler effect; law of snel; radar